FeReRe: Feedback Requirements Relation using Large Language Models [data] - Anders, Michael (Universität, 2025)
This dataset consists of 3 parts: The "related_work.bib" contains citations for the Related Work section of the paper. The "ChatGPTPrompts.xlsx" contains a list of all prompt experiments conducted with ChatGPT on the Komoot dataset, including the final prompts and results. The "data" folder contains all 4 datasets used for training and testing of the BERT classifier in the paper. Each dataset contains feedback, requirements and a ground truth in which feedback IDs are assigned to requirement IDs. The folder can be copied into the FeReRe code (https://github.com/feeduvl/FeReRe) to reproduce results.